Double-grafted chitosans as siRNA nanocarriers: effects of diisopropylethylamine substitution and labile-PEG coating - Martinez Junior, Andre Miguel [UNESP]; Felix Viegas de Souza, Ricchard Hallan [UNESP]; Petronio, Maicon Segalla [UNESP]; Martins, Grazieli Olinda [UNESP]; Fernandes, Julio Cesar; Benderdour, Mohamed; Oliveira de Tiera, Vera Aparecida [UNESP]; Tiera, Marcio Jose [UNESP] (Springer, 2022)
The preparation of safe and efficient siRNA carriers remains a challenge that has limited the therapeutic applications of siRNA. In this study, the design of a new small interfering RNA (siRNA) carrier based on diisopropylaminoethyl-chitosan was devised for application in non-viral gene therapy. Polycations having varied proportions (11-32%) of diisopropylethylamine groups (DIPEA) and grafted with polyethylene glycol (1-3%) were synthesized and characterized. The physicochemical and biological properties of the polymers and their nanoparticles were evaluated at pH 6.3 and pH 7.4. The degrees of ionization at pH 7.4 were precisely controlled by the composition and increased from 13% for chitosan to 47% for the more substituted derivative. Nanoparticles with very low toxicities and sizes in the range of 100-200 nm, remained stable up to 24 h after their preparation in both the evaluated pHs under plasma osmolality. As probed by scanning electron and confocal microscopies, an efficient cell uptake of spherical nanoparticles mediated a TNF alpha knockdown of almost 60% in RAW 264.7 macrophages, and mRNA silence levels higher than the Lipofectamine (up to 90%) in HeLa cells. Overall, the results showed that these derivatives are promising vectors for in vivo studies under physiological conditions.
Keywords: siRNA; DIPEA; Nanoparticles; Knockdown; Non-viral vector; Gene therapy; TNF alpha